Silver Bullet or Ricochet? CEOs’ Use of Metaphorical Communication and Infomediaries’ Evaluations - König, Andreas; Mammen, Jan; Luger, Johannes; Fehn, Angela; Enders, Albrecht (Academy of Management Journal, 2018)
We combine literature on rhetoric and socially situated sensemaking to illuminate the challenges that emerge when chief executive officers (CEOs) try to influence infomediaries by using metaphorical communication—figurative linguistic expressions that convey thoughts and feelings by describing one domain, A, through another domain, B. Specifically, we theorize that because different infomediaries are situated in different thought worlds, CEOs’ use of metaphorical communication has contradictory effects on journalists’ and securities analysts’ evaluations: while it triggers more favorable statements from journalists, it prompts more unfavorable assessments from analysts. Moreover, we integrate findings from cognitive psychology to argue that these contradictory effects increase the more a firm’s performance falls behind market expectations. Our hypotheses find support in an extensive analysis of 937 quarterly earnings calls in the U.S. pharmaceutical, hardware, and software industries, and of journalists’ statements and analysts’ earnings forecasts and recommendations. Our novel theorizing and findings suggest that the use of discursive frames, especially in the form of metaphorical communication, in firms’ interactions with critical audiences creates thought-provoking and thus-far neglected dilemmas. In developing and testing these thoughts, we contribute to and link ongoing conversations in management science, especially discussions of organizational reputation, executive communication, and impression management.